Genotypic study documents divergence in the pathogenesis of bloodstream infection related central venous catheters in neonates - Brito,Cristiane Silveira (2014)
OBJECTIVE: To investigate the pathogenesis of bloodstream infection by Staphylococcus epidermidis, using the molecular epidemiology, in high-risk neonates. METHODS: We conducted a prospective study of a cohort of neonates with bloodstream infection using central venous catheters for more than 24 h. "National Healthcare Safety Network" surveillance was conducted. Genotyping was performed by DNA fingerprinting and mecA genes and icaAD were detected by multiplex-PCR. RESULTS: From April 2006 to April 2008, the incidence of bloodstream infection and central venous catheter-associated bloodstream infection was 15.1 and 13.0/1000 catheter days, respectively, with S. epidermidis accounting for 42.9% of episodes. Molecular analysis was used to document the similarity among six isolates of bloodstream infection by S. epidermidis from cases with positive blood and central venous catheter tip cultures. Fifty percent of neonates had bloodstream infection not identified as definite or probable central venous catheter-related bloodstream infection. Only one case was considered as definite central venous catheter-related bloodstream infection and was extraluminally acquired; the remaining were considered probable central venous catheter-related bloodstream infections, with one probable extraluminally and another probable intraluminally acquired bloodstream infection. Additionally, among mecA+ and icaAD+ samples, one clone (A) was predominant (80%). A polyclonal profile was found among sensitive samples that were not carriers of the icaAD gene. CONCLUSIONS: The majority of infections caused by S. epidermidis in neonates had an unknown origin, although 33.3% appeared to have been acquired intraluminally and extraluminally. We observed a polyclonal profile between sensitive samples and a prevalent clone (A) between resistant samples.